134 The major incident app- an improved way to contact staff in major incidents. Issue 12 (23rd November 2020) - Hulme, Peter; Madden, Alannah; Reynard, Charlie
Abstract : Aims/Objectives/Background: Major incidents are thankfully rare events but require appropriate planning and training to ensure the best response for patients and staff. The method of contacting staff in these incidents is key and needs to be quick, reliable and have excellent response times to be effective. The best method of contacting staff has not been ascertained. The Major Incident App (MIA) is a new way to contact staff in major incidents and sends loud alerts even when phones are on silent mode. This study looks to compare the major incident response times using MIA with the previous way of contacting staff in a major incident- a freely available digital messaging platform (DMP) at Manchester Foundation Trust. Methods/Design: The decision to declare a major incident or standby was determined by the consultant in Emergency Medicine who was in the department at the time of the incident. The receiving consultants would read the message as soon as they saw it and respond appropriately. After the incidents we conducted a retrospective review of digital communication records to ascertain the time taken for a DMP or MIA message declaring an incident to be seen and read by the receiving consultants. Reading the message within 15 minutes was regarded as an 'excellent' response time and within 60 minutes was regarded as a 'good' response. These time intervals were determined by the expert opinion of five Major Trauma consultant experts at Manchester Foundation Trust. A Wilcoxon rank sum test was used to compare the two methods. Results/Conclusions: Response times were significantly better with MIA compared to DMP p-value<0.001 (see Tables 1 and 2) and all messages were seen within 4 minutes. Although the numbers of incidents are small, this study shows that incident response times can be significantly improved with the MIA that alerts phones in silent mode.